THE PSYCHOLOGY ELEMENT BY CHARACTER FROM NOVEL "BREATH OF SCANDAL" BY SANDRA BROWN - Haris, Shita Sukmaningsih; Nur, Sahril; Nur, Muh Safar (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
This research aimed to find out the operant conditioning that occurs to the main character in the novel Breath of Scandal and the impacts of operant conditioning on the character using literary psychological approach. This research approach combines interactive data analysis with descriptive qualitative methodologies, which is the process of processing data by collecting, selecting, and connecting it in a systematic way in order to reach conclusions. The source is from “Breath of Scandal” novel that is written by Sandra Brown. The novel's operant conditioning, which is assisted by behaviorism theory, develops through Jade's major characters' humiliation, harassment, and betrayal by her best friend, childhood friend, lover, and parents as well as through her encouragement, acceptance, and revenge. The result of this study showed twenty-eight extracts of operant conditioning that have been associated with behaviorism theory written in the novel. Fourteen out of twenty-eight were stimulus to Jade as the main character, and fourteen were responses from Jade. The result of the research showed that operant conditioning did happen to Jade as the main character, but it could not be determined like in the live experiments, and the impact of the operant conditioning on Jade is making it hard for her to forgive and to believe in someone throughout the novel's plot.